Step-by-step
Simplifying 2a + 3 = 4a + 5
Reorder the terms: 3 + 2a = 4a + 5
Reorder the terms: 3 + 2a = 5 + 4a
Solving 3 + 2a = 5 + 4a
Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right.
Add '-4a' to each side of the equation. 3 + 2a + -4a = 5 + 4a + -4a
Combine like terms: 2a + -4a = -2a 3 + -2a = 5 + 4a + -4a Combine like terms: 4a + -4a = 0 3 + -2a = 5 + 0 3 + -2a = 5 Add '-3' to each side of the equation. 3 + -3 + -2a = 5 + -3 Combine like terms: 3 + -3 = 0 0 + -2a = 5 + -3 -2a = 5 + -3 Combine like terms: 5 + -3 = 2 -2a = 2 Divide each side by '-2'. a = -1 Simplifying a = -1